Purification and characterization of an antioxidant protein (similar to 16 kDa) from Terminalia chebula fruit - Srivastava, Pratibha; Raut, Hema N.; Wagh, Renuka S.; Puntambekar, Hemalata M.; Kulkarni, Mahesh J. (Food Chemistry, 2012)
Terminalia chebula fruit is used as folk medicine in India and Southeast Asia. An antioxidant protein was isolated by bioassay guided fractionation of T. chebula fruit by homogenizing in the citrate phosphate buffer. The isolated protein (TCP-III) obtained from fruit was purified by gel chromatography and preparative HPLC, showed apparent molecular weight of 16 kDa by SDS-PAGE and MALDI-TOF/MS analyses. Amino acid sequence obtained by LC-MSE analysis showed homology with the predicted protein fragments of Populus trichocarpa, putative uncharacterized protein fragments from Oryza sativa and with fragments of 17 kDa thylakoid lumenal protein from Spinacia oleracea. TCP-III exhibited significant radical scavenging in DPPH, NO, H2O2 and ABTS assays. In addition, TCP-III inhibited oxidation of linoleic acid in beta-carotene bleaching assay, reduced ferric ions and chelated ferrous ions. The present finding demonstrates uniquely, for the first time, characterization of an antioxidant protein from T. chebula fruit. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: 16 kDa protein molecule of T. chebula; Antioxidant and free radical scavenging activity; Characterization; Purification; Terminalia chebula fruit

Molecular modeling studies and in vitro screening of dihydrorugosaflavonoid and its derivatives against mycobacterium tuberculosis - Puranik, Ninad V.; Srivastava, Pratibha; Swami, Sagar; Choudhari, Amit; Sarkar, Dhiman (RSC Advances, 2018)
Novel drug regimens against tuberculosis (TB) are urgently needed and may be developed by targeting essential enzymes of Mtb that sustain the pathogenicity of tuberculosis. In the present investigation, series of compounds (5a-f and 6a-f) based on a naturally occurring rugosaflavonoid moiety were evaluated by in silico molecular modeling studies against -ketoacyl-ACP reductase (MabA) (PDB ID: IUZN) and pantothenate kinase (PanK) (PDB ID: ; 3AF3). Compounds 5a, 5c, 5d, and 6c, which had docking scores of -8.29, -8.36, -8.17 and -7.39 kcal mol(-1), respectively, displayed interactions with MabA that were better than those of isoniazid (-6.81 kcal mol(-1)). Similarly, compounds 5a, 5c, 5d, and 6c, which had docking scores of -7.55, -7.64, -7.40 and -6.7 kcal mol(-1), respectively, displayed interactions with PanK that were comparable to those of isoniazid (-7.64 kcal mol(-1)). Because of their docking scores, these compounds were screened in vitro against Mycobacterium tuberculosis H37Ra (Mtb) using an XRMA protocol. Among the screened compounds, the dihydrorugosaflavonoid derivatives 5a, 5c, and 5d had IC50 values of 12.93, 8.43 and 11.3 g mL(-1), respectively, and exhibited better inhibitory activity than the parent rugosaflavonoid derivatives. The rugosaflavonoid derivative 6c had an IC50 value of 17.57 g mL(-1). The synthesized compounds also displayed inhibitory activity against the Gram-positive bacteria Bacillus subtilis and Staphylococcus aureus. The present study will be helpful for the further development of these molecules into antitubercular lead candidates.

First synthesis of podocarflavone A and its analogs and evaluation of their antimycobacterial potential against mycobacterium tuberculosis with the support of virtual screening - Puranik, Ninad V.; Swami, Sagar; Misar, Ashwini V.; Mamgain, Ritu; Gulawani, Swapnaja S.; Dhiman, Sarkar; Srivastava, Pratibha (Natural Product Research, 2022)
The first synthetic route developed for Podocarflavone A reported from Podocarpus macrophyllus and its analogs in 7 steps. Computational analysis for binding with the pantothenate kinase (3AVO) of Mycobacterium tuberculosis showed their docking score (ds) in the range of -8.9 to -9.3 Kcal/mol. MD simulations delineated the stability of the protein-ligand complexes in the TIP3P model. MMGBSA and MMPBSA values of 8d were -42.46 Kcal/mol and -14.58 Kcal/mol, respectively. Further in-vitro antitubercular screening of compounds 8a, 8d, and 8e against M. tuberculosis H37Ra using XRMA protocol exhibited promising antimycobacterial activity with IC50 values 21.82 mu g/mL, 15.55 mu g/mL, and 16.56 mu g/mL, respectively. Compounds 8a, 8d, and 8e showed antibacterial activity with IC50 values 41.56 mu g/mL, 24.72 mu g/mL, and 72.45 mu g/mL respectively against the Staphylococcus aureus. 8a and 8d showed inhibition with IC50 values 39.6 mu g/mL and 27.64 mu g/mL, respectively, against Bacillus subtilis. The present study could help in the further development of lead molecules against tuberculosis.
Keywords: and MMGBSA; antimycobacterial activity; docking; MD simulations; MMPBSA; Podocarflavone A synthesis

Design, synthesis, and in vitro biological evaluation of ROS-generating phenanthridin-trione-epoxide conjugates as agents against mycobacterium tuberculosis - Mamgain, Ritu; Swami, Sagar; Sarkar, Dhiman; Srivastava, Pratibha (ChemistrySelect, 2023)
Tuberculosis (TB) is one of the devasting infectious diseases and continues to spread among people despite having several specific drugs. Total eradication of TB is one of the shared interests of both the World Health Organization (WHO) and India globally. A library of antitubercular 6-((1-(aryl/heteroaryl)-1H-1,2,3-triazol-4-yl)methyl)oxireno[2,3-b] phenanthridine-5,7,9(6H,7aH,8aH)-trione (6 a-e) has been prepared in five steps including click chemistry and tested against active and dormant strains of Mycobacterium tuberculosis H37Ra using XRMA protocol. The result showed the inhibitory potential of 6 d IC50 at 0.74 & mu;g/mL concentration against active strain and at 0.9 & mu;g/mL against the dormant strain of Mtb. ROS generating ability of the compounds has been confirmed by luminol, H2O2, and glutathione assays. The molecular docking with the thioredoxin protein of Mtb showed a docking score of -9.6 Kcal/mol. To understand the mechanism with the thioredoxin protein of Mtb, the adduct formation of compounds with cystine was confirmed with HPLC. The involvement of lead molecules with existing drugs can be helpful in the eradication of tuberculosis.
Keywords: antimycobacterial agents; Computational docking; Cystine adduct; Epoxy-Phenanthridinone-triazoles; ROS generation